2011
DOI: 10.1007/s10404-011-0890-6
|View full text |Cite
|
Sign up to set email alerts
|

Microfluidic systems for the analysis of viscoelastic fluid flow phenomena in porous media

Abstract: The Strathprints institutional repository (https://strathprints.strath.ac.uk) is a digital archive of University of Strathclyde research outputs. It has been developed to disseminate open access research outputs, expose data about those outputs, and enable the management and persistent access to Strathclyde's intellectual output. RESEARCH PAPERMicrofluidic systems for the analysis of viscoelastic fluid flow phenomena in porous media Abstract In this study, two microfluidic devices are proposed as simplified 1-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
63
1
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(73 citation statements)
references
References 46 publications
7
63
1
2
Order By: Relevance
“…25) as related to extensional flows as the fluid flows through contractions. 26 However, more recent experimental results 27 in model geometries indicate that the succession of converging/diverging flows has little effect on the pressure gradient as compared to the curvature of the streamlines which promote unsteady flows. Generally speaking, the general description of flow of viscoelastic liquids in porous media remains an open issue (see, for example, Ref.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…25) as related to extensional flows as the fluid flows through contractions. 26 However, more recent experimental results 27 in model geometries indicate that the succession of converging/diverging flows has little effect on the pressure gradient as compared to the curvature of the streamlines which promote unsteady flows. Generally speaking, the general description of flow of viscoelastic liquids in porous media remains an open issue (see, for example, Ref.…”
Section: Introductionmentioning
confidence: 99%
“…However, for the relatively small contractions in the studied micromodel (the relative standard deviation of channel width is 0.33), studies have shown that the corresponding extra pressure remain weak. 26,27 It is interesting to discuss the value of Wi c . Elastic instabilities are known to occur in curvilinear flow above a threshold given by a criterion proposed by McKinley et al, 11 with Wi ffiffiffiffiffiffiffiffiffiffi w=R p > M, where R is the radius of curvature of the streamlines.…”
mentioning
confidence: 99%
“…For these liquids pressure versus flow rate experiments have been conducted, not only in porous media and packed beds, but also in artificially made geometries that mimic the conditions in a porous medium [1][2][3][4]. From these studies, the following picture has emerged.…”
Section: Introductionmentioning
confidence: 99%
“…As it was mentioned previously, at the micro-scales (typical scales from the human circulatory system), the elastic effects are enhanced even at low Reynolds numbers [7,54,55]. The complex rheological behaviour of whole blood has been studied and continues to be investigated using new technological advances [56,57].…”
Section: Complex Fluids In the Human Body For Blood Flowmentioning
confidence: 95%